The Assessment of Evidence Associating Nonsteroidal Anti-Inflammatory Drugs with Complications of Peptic Ulcerations - MJS Langman (Canadian Journal of Gastroenterology)
A causal relationship is now firmly established between nonsteroidal anti-inflammatory drug (NSAlD) use and the occurrence of peptic ulcer complications. In the United Kingdom, rising NSAID use has been matched by rises in ulcer mortality and perforation rates, particularly in older women. It is not likely, however, that drug use accounts for the entire increase. The reasons why some people develop ulcer complications and others do not are poorly understood. It is plausible to propose that other factors, such as history of ulcer or indigestion, current smoking, and alcohol consumption, might raise this risk; however, supportive evidence is lacking.